The REMEDEE trial: 5‐Year results on a novel combined sirolimus‐eluting and endothelial progenitor cells capturing stent. Issue 6 (5th September 2019) - Haude, Michael; Lee, Stephen W. L.; Worthley, Stephen G.; Silber, Sigmund; Verheye, Stefan; Rosli, Mohd A.; Botelho, Roberto; Sim, Kui H.; Abizaid, Alexandre; Mehran, Roxana; ,
Abstract: Objectives: To evaluate the long‐term safety and efficacy of the novel combined sirolimus‐eluting endothelial progenitor cell capture Combo stent (OrbusNeich, Fort Lauderdale, FL) at 5 years in the REMEDEE (Randomized study to Evaluate the safety and effectiveness of an abluMinal sirolimus coated bio‐Engineered stEnt) trial. Background: Drug–eluting stents have limited restenosis and reintervention but are complicated by late and very late thrombosis and accelerated neoatherosclerosis. Alternative or adjunctive technologies are needed to address these limitations. Methods: A total of 183 patients with de novo lesions in native coronary arteries were randomized 2:1 to Combo ( n = 124) or Taxus Liberté ( n = 59). Primary endpoint was 9 month angiographic in‐stent late lumen loss and the secondary endpoint was the occurrence of major adverse events (MACE) through 5‐year follow‐up. Results: Compared with Taxus, after 5 years the Combo stent was associated with similar rates of MACE (18.3% vs. 16.9%, p = .89), cardiac death (0.8% vs. 5.1%, p = .07), myocardial infarction (4.1% vs. 3.4%, p = .81), target lesion (9.4% vs. 10.2%, p = .78), and target vessel revascularization (14.4% vs. 11.9%, p = .73). No cases of definite stent thrombosis were reported in the Combo group. The follow‐up rate at 5 years was 97.7%. Conclusion: At 5‐year follow‐up, the Combo stent remained clinically safe and effective with an overall low rate of MACE comparable to Taxus.